Co-production of hydrogen and ethanol by Escherichia coli SS1 and its recombinant - Soo, Chiu Shyan; Yap, Wai Sum; Hon, Wei Min; Ramli, Norhayati; Md Shah, Umi Kalsom; Phang, Lai-Yee (Pontificia Universidad Católica de Valparaíso, 2017)
Background The development of a potential single culture that can co-produce hydrogen and ethanol is beneficial for industrial application. Strain improvement via molecular approach was proposed on hydrogen and ethanol co-producing bacterium, Escherichia coli SS1. Thus, the effect of additional copy of native hydrogenase gene hybC on hydrogen and ethanol co-production by E. coli SS1 was investigated.